The effect of gymnastics on changes in nutritional status and physical fitness levels in overweight and obese adolescents - Iriyani K Iriyani K; Faisal Anwar; Lilik Kustiyah; Hadi Riyadi (AcTion: Aceh Nutrition Journal, 2023)
Gymnastics is a sport that affects the BMI and physical fitness of overweight and obese adolescents. Overweight and obesity occur due to an imbalance in energy intake and expenditure and a decrease in physical activity, which can cause adolescent health problems. This study aims to analyze the effect of physical fitness gymnastics on changes in BMI and physical fitness of overweight and obese adolescents. The research design is a quasi-experimental pre-post intervention study. The research was conducted at the 2nd and 3rd State Junior High Schools in Samarinda City, from November 2020 to January 2021. A sample of 38 people was selected using purposive sampling. Data collection was collected by weighing, measuring height, and measuring nutritional status using BMI for age. Fitness data obtained from IPFT measurement results. Statistical analysis using T-tests. The results showed that there was no difference in body weight and fitness before and after exercise intervention in the two groups (overweight and obese) (p>0,05), but BMI for age showed a difference before and after (p<0,05). With the difference in changes in body weight (2,35 ± 0,85 kg), BMI for age (0,52 ± 18,43), and increased fitness (2,86 ± 2,50). In conclusion, the physical fitness exercise intervention affected changes in body weight, BMI for age, and physical fitness of overweight and obese adolescents, which was carried out for 12 weeks with a frequency of 5 times per week for 30 minutes.